Pengujian dan Model Penerimaan Aplikasi Web Mapping System Lahan Pertanian - Delfia Balisa; Rosa Delima; Antonius Rachmat Chrismanto; Halim Budi Santoso (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The entry of technology in agriculture also has a big influence in supporting farmers in making their work easier. Many agricultural systems are formed that can encourage the success of farming productivity, such as an example of a system for collecting farmer data and farming activities, a land management system, land preparation so that a system that provides information as learning for farmers and farmer groups. In this study, the usability test and acceptance test of the web application mapping system for agricultural land will be carried out to see the level of reusability and the level of acceptance of the system. Usability testing uses the usability testing method, while acceptance testing uses the technology acceptance model method and uses an eye tracker in testing and the Partial Least Square software to process data. The results of this study indicate the level of usability of the combining metrics task success is 93%, time on task is 43%, error is 60% and efficiency is 70%. For the results of the acceptance test, it was obtained that two of the five hypotheses had a significant and significant influence, namely the perceived ease of perception on the perceived usefulness and the perceived attitude of use towards behavioral interest.